The Association between Isometric Cervical Extension Force and Dimensions of Semispinalis Capitis Muscle - Asghar Reza-ُُُSoltani; Mohsen Amiri; Khosro Khademi-Kalantari; Hassan Namvar; Elaheh Sajadi; Parisa Mirhaji-Maghamjoo'ee (University of Social Welfare and Rehabilitation Sciences, 2011)
Objective: The anatomy of the human cervical region has a special complexity. Ultrasonography is a scanning technique, which has been successfully used to identify and measure the cervical muscle dimensions. The purpose of this study was to detect the dimensional changes of the human Semispinalis Capitis Muscle (SECM) with Real Time Ultrasound (RTUS) during isometric cervical extension. Materials & Methods: Six junior ice hockey players took part in the study. We simultaneously measured the values of estimates, such as breadth or anteroposterior dimension (APD) and width or lateral dimension (LD), of the SECM cross-sectional area during isometric cervical extension at different maximum voluntary contraction (MVC) percentile levels (0%, 20%, 40%, 60%, 80%, and 100%). Results: The result of multiplication of the linear dimensions (APD×LD), considered as the size of the SECM, increased (P<0.05) with rising the level of the cervical extension force. The correlation between muscle size and extension force of 100% MVC was  r = 0.79 (P =0.05). Conclusion: The Real Time Ultrasound method may be useful in evaluating the function of each individual cervical muscle.